Terra sigillata worskshop at Margum, Upper Moesia - Cvjetićanin, Tatjana (Rei Cretariae Romanae Fautorum Acta, 2015)
In the National Museum collection there are fragments of four moulds of Drag. 37 vessels, from Margum, purchased in 1973 from Radiša Vujičić. Motives are well known in the repertoire of Viminacium-Margum workshop (running deer, dog; six-bordered ovoli, row of rosettes beneath with running dog, five-bordered ovoli scattered in the decorative field), but not particular organization of elements and arrangement. These unpublished moulds, as well as new excavations of Margum launched in 2011, were reason for this re-consideration of the Viminacium-Margum terra sigillata workshop.